A Practical Guide to Levitation: Stories by José Eduardo Agualusa - Nyathi, Jacqueline (New Agenda: SA Journal of Social and Economic Policy, 2024)
Mozambique-based writer José Eduardo Agualusa and his wonderful translator, Daniel Hahn, have a way with words, the fantastical and the surreal. They bring ghosts to life with dry humour, and immerse us in alternate cosmologies, showing us other ways the world might be.